gedächtnisRäume : Hommage für Miklós Erdély : Filme - Installationen - Performances - Vorträge. - Künstlerhaus Bethanien, Berlin; Haus Ungarn, Berlin (Berlin : Künstlerhaus Bethanien, 1992)
be, Käthe ; Börocz, Andras ; Bukta, Imre ; de Chirico, Jakob ; Gémes, Péter ; Halász, Károly ; limura, Takahiko ; Karawahn, Kain ; Kiss, Péter ; Lugossy, Laszlo fe. ; Sugar, Janos ; Szirtes, Janos ; Trombitas, Tamas ; Thomas, Angelika
gedächtnisRäume : Hommage für Miklós Erdély : Filme - Installationen - Performances - Vorträge, Künstlerhaus Bethanien, Berlin
The catalogue gedächtnisRäume was published on the occasion of the performance festival within the series of events grenzenlos, KULTURELLE BEGEGNUNG: BUDAPEST-BERLIN in cooperation with Haus Ungarn
boek